Thermal analysis of a 1-kW hydrogen-fueled solid oxide fuel cell stack by three-dimensional numerical simulation - Kim, Dong Hwan; Bae, Yonggyun; Lee, Sanghyeok; Son, Ji-Won; Shim, Joon Hyung; Hong, Jongsup (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
This study aims at elucidating the thermal characteristics and heat transfer mechanism of a commercial-scale, planar solid oxide fuel cell (SOFC) stack. The thermal management of a SOFC stack is key for its stable operation and market deployment. It is necessary to understand the internal thermal conditions and heat transfer pathways for satisfying such needs. In this regard, this study conducts three-dimensional numerical simulation accounting for an actual 1-kW stack geometry and its operating conditions. The thermal-flow conditions of the stack composed of 30 unit-cells are spatially resolved. Results show that temperature inside a stack changes in a way that it follows the air flow. As the air and fuel proceed to the top of the stack, the effect of the air flow is more prominent while showing a smaller temperature difference of unit-cells inside a repeating unit and a lower rate of its temperature increase. Given the temperature distribution, a large temperature gradient is imposed on unit cells and sealants near the air inlet, especially in the lower repeating units. It is also shown that, in the direction of stack height, gaseous advection is a key pathway through which the heat released from a unit-cell is transferred, and conductive heat transfer through metallic interconnects contributes to the overall heat transfer rate at the top and bottom of the stack. As the gaseous advective cooling in the direction of stack height is reduced, the heat transfer rates towards the gas inlets and outlets within a repeating unit by interconnect conduction and gaseous advection, respectively, are also lowered, which is compensated by conductive heat transfer between repeating units. It can be inferred that controlling gas heating near the inlet manifold (especially, at the bottom of the stack), advection through the stack, and metallic conduction between repeating units may change the key heat transfer pathways and internal thermal conditions.
Keywords: FLOW DISTRIBUTION; COMBINED HEAT; MODELING TOOL; DESIGN; SYSTEM; OPTIMIZATION; ELECTROCHEMISTRY; PREDICTION; STABILITY